Common and rare CARD14 gene variants affect the antitumour necrosis factor response among patients with psoriasis. (25th April 2016) - Coto‐Segura, P.; González‐Fernández, D.; Batalla, A.; Gómez, J.; González‐Lara, L.; Queiro, R.; Alonso, B.; Iglesias, S.; Coto, E.
Summary: Background: The CARD14 gene encodes a protein that enhances nuclear factor (NF)‐κB activation and the upregulation of proinflammatory pathway genes. CARD14 is upregulated in psoriatic vs. normal skin, and rare and common CARD14 variants have been associated with the risk of developing psoriasis. Our hypothesis was that CARD14 variants could also influence the response to antitumour necrosis factor (anti‐TNF) therapies among patients with psoriasis. Objectives: To determine whether CARD14 gene variants were linked to a significant positive anti‐TNF response in patients with psoriasis. Methods: DNA from 116 patients with psoriasis was subjected to next‐generation sequencing of the CARD14 gene. All of the patients were nonresponders or had contraindications to conventional systemic treatments. Results: A reduction of at least 75% in Psoriasis Area and Severity Index (PASI 75) at week 24 was considered a positive response to treatment. In total 116 patients (79 responders and 37 nonresponders) were next‐generation sequenced, and we identified five nucleotide variants that would result in missense amino acid changes. These variants were determined in all of the patients, and allele and genotype frequencies were compared between the two groups. We found a significantly higher frequency of rs11652075 CC (p.Arg820Trp) among the group with a positive response ( P = 0.01, odds ratio 3.71, 95% confidence interval 1.30–10.51). Furthermore, among responders, six patients were heterozygous carriers of the rare p.Glu422Lys variant, and two patients were heterozygous for p.Arg682Trp ( P = 0.04). Conclusions: The common CARD14 p.Arg820Trp variant might have a significant effect on the response to anti‐TNF therapies among patients with psoriasis. In addition, rare CARD14 missense variants could also predispose to a better response. Abstract : What's already known about this topic? Patients with psoriasis treated with antitumour necrosis factor (anti‐TNF) agents (and other biological therapies) exhibit a heterogeneous response. This could be explained partly by the variability in genes that encode components of immunological pathways. Rare and common CARD14 variants have been linked to the risk for psoriasis, but no study about the effect on anti‐TNF response has been reported. What does this study add? Our study showed that the CARD14 rs11652075 polymorphism (Arg820Trp) was associated with the response to anti‐TNF agents among patients with psoriasis. The genotype that increased the risk for psoriasis was also a significant predictor of a better anti‐TNF response, measured as ≥ 75% improvement in Psoriasis Area and Severity Index at week 24. What is the translational message? Variants of the CARD14 gene (a regulator of nuclear factor‐κB‐mediated pathways) have been associated with the overall risk of developing psoriasis in case–control studies. In this work, we show that CARD14 variants are also related to the response to anti‐TNF agents. If the results are confirmed by others, the analysis of this gene might help dermatologists to optimize treatment with anti‐TNF biological drugs. Linked Comment: Wu and Reynolds. Br J Dermatol 2016; 175 :17–18